Geochemistry of biotite from Kuala Lumpur Granite - A. Ghani, Azman (Malaysian Journal of Science, 2002)
This work presents a new biotite analyses of Kuala Lumpur granite. The biotites have been analysed from three different samples namely equigranular normal biotite-muscovite granite (NBMG), deformed muscovite granite (DBMG) and porphyritic biotite-muscovite granite (PBMG). Geochemistry of the biotite is similar to the biotite crystallised from peraluminious melt, characterised by high $Al_{2}0_{3}$. The compositions of the biotite under study were defined by $F0_2$ near to that of the $Si0_2$-$Fe_{2}SiO_{4}$-$Fe_{3}0_{4}$ buffer.